1988
DOI: 10.1111/j.1748-1716.1988.tb08298.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of renal denervation on vascular responsiveness of isolated rat intrarenal arteries

Abstract: Microsurgical renal denervation of the rat has been reported to increase blood loss and bleeding time after a standardized kidney resection. To investigate the vascular effects of denervation, isolated intrarenal arteries were studied using sensitive 'isometric' recording equipment. Four pieces of evidence were obtained to indicate an effective functional denervation I week after renal nerve transection: (i) Phentolamine reduced the K+-induced contraction in controls but not in denervated arteries. (ii) The K+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…In rat interlobar arteries, Ang I and II were reported to have no contractile effects approximately 1 week after renal denervation (13). Eighteen weeks after denervation, we found constrictor responses to Ang II of similar intensity in small vessels isolated from denervated and native kidneys.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…In rat interlobar arteries, Ang I and II were reported to have no contractile effects approximately 1 week after renal denervation (13). Eighteen weeks after denervation, we found constrictor responses to Ang II of similar intensity in small vessels isolated from denervated and native kidneys.…”
Section: Discussionmentioning
confidence: 53%
“…The present study reveals that, 18 weeks after denervation of single kidneys, the responses of small renal vessels to AVP is not elevated compared with resistance vessels from native single kidneys or vessels from kidneys of rats that did not undergo any surgery. However, 1 week after denervation, responsiveness of renal interlobular arteries to AVP has been reported to be increased (13). Plasma concentrations of Ang II and AVP levels are elevated in patients with chronic renal failure.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…) and others (Hogestatt et al . ) showing that systemic sympathectomy or topical renal denervation elicited supersensitivity to adrenergic stimulation in intrarenal arteries. Together, these findings suggest that renal pelvic and vascular smooth muscle differ from each other with respect to the consequences of chronic removal of sympathetic tone on agonist‐induced contractile responses.…”
Section: Discussionmentioning
confidence: 99%
“…As it has been shown that the denervation‐induced supersensitivity of vascular smooth muscle extends beyond adrenergic stimulation to also affect non‐adrenergic stimuli (Hogestatt et al . , Grisk et al . ), we opted to investigate the responses of renal pelves from transplanted and non‐transplanted solitary kidneys to ET‐1.…”
Section: Discussionmentioning
confidence: 99%